2013
DOI: 10.1021/nl401070p
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance, Transparent, and Stretchable Electrodes Using Graphene–Metal Nanowire Hybrid Structures

Abstract: Transparent electrodes that can remain electrically conductive and stable under large mechanical deformations are highly desirable for applications in flexible and wearable electronics. This paper describes a comprehensive study of the electrical, optical, and mechanical properties of hybrid nanostructures based on two-dimensional graphene and networks of one-dimensional metal nanowires, and their use as transparent and stretchable electrodes. Low sheet resistance (33 Ω/sq) with high transmittance (94% in visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
455
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 610 publications
(472 citation statements)
references
References 41 publications
9
455
0
1
Order By: Relevance
“…Copyright 2010, American Chemical Society. c,d) Reproduced with permission 70. Copyright 2013, American Chemical Society.…”
Section: Properties and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2010, American Chemical Society. c,d) Reproduced with permission 70. Copyright 2013, American Chemical Society.…”
Section: Properties and Preparationmentioning
confidence: 99%
“…Hence, beyond chemical doping mentioned above, hybrid structures, e.g., introducing CNTs68, 69 or metal nanostructures70, 71, 72, 73 also have been developed to solve this problem in recent years.…”
Section: Properties and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybridization of AgNWs with other nanomaterials, such as graphene and CNTs, further improves the electrical and mechanical properties of the resulting stretchable and transparent electrodes [3,[28][29][30][31][32][33][34]. For example, the introduction of graphene onto an AgNWbased percolation network (Figure 1(d)) provides additional conducting paths through the two-dimensional structure of graphene beyond the one-dimensional paths of AgNWs, resulting in improved conductivity compared to the AgNW-only electrode.…”
Section: Ag Nanowiresmentioning
confidence: 99%
“…Also, the low moisture permeability of graphene leads to the enhanced longterm stability of the graphene-AgNW hybrid electrode compared to the AgNW-only counterpart [31]. Park et al demonstrated an AgNW-graphene hybrid transparent electrode, which showed excellent optical transmittance (94% in the visible range) and low sheet resistance (33 /sq) as well as 100% stretchability without significant resistance changes [28]. Figure 1(e) shows the implementation of a display pixel on a contact lens using this AgNW-graphene hybrid electrode.…”
Section: Ag Nanowiresmentioning
confidence: 99%